Solutions to Lyapunov stability problems: nonlinear systems with continuous motions - Ljubomir T. Grujic (International Journal of Mathematics and Mathematical Sciences)
The necessary and sufficient conditions for accurate construction of a Lyapunov function and the necessary and sufficient conditions for a set to be the asymptotic stability domain are algorithmically solved for a nonlinear dynamical system with continuous motions. The conditions are established by utilizing properties of o-uniquely bounded sets, which are explained in the paper. They allow arbitrary selection of an o-uniquely bounded set to generate a Lyapunov function.